Human remains from Ntshekane, an Early Iron Age site in central KwaZulu-Natal - Owens, Lawrence S.; Thorp, Carolyn; Whitelaw, Gavin (Southern African Humanities, 2023)
Research at the Early Iron Age site of Ntshekane in central KwaZulu-Natal, South Africa, recovered human skeletal remains representing a pregnant adult, two young adults and two infants. All were exposed by severe erosion. Ceramics and an interpretation of settlement history at Ntshekane suggest an infant buried in a grain pit dates to the Msuluzi phase (630–800), one young adult to either the Ndondondwane (800–950) or Ntshekane (950–1050) phase, the second young adult to the Ntshekane phase, with the pregnant woman and possibly the second infant belonging to the Ntshekane phase. The dentition of the pregnant woman and a modified tooth associated with the remains of one young adult indicate the practice of dental modification. Differences in the interments of the two infants possibly relate to the circumstances of their deaths.